Pengaruh Pengungkapan Pada Sustainability Report Terhadap Kinerja Keuangan Perusahaan - Anisah, Nur; Silfia, Fadia Ayu (Jurusan Akuntansi Politeknik Negeri Padang, 2023)
The aim of this research is to examine the effect of disclosure in sustainability reports which include economic aspects, environmental aspects and social aspects on the company's financial performance (Return On Assets). The Global Reporting Initiative (GRI) G4 standard, which consists of 91 items, is used as a guideline for disclosing sustainability reports. The population of this research are companies listed on the IDX30 Index of the Indonesian Stock Exchange between 2018-2022. Using a purposive sampling approach, 13 companies were selected as research samples. The findings of this research show that disclosure of economic aspects has a significant positive effect on the company's financial performance, disclosure of environmental aspects has no effect on the company's financial performance, and disclosure of social aspects has a significant negative effect on the company's financial performance. The results of this research provide implications for company management to consider sustainability issues in improving the company's financial performance and as information for investors in determining investment decisions.